Basic Concepts of Sharia Money Market - Nuryani, Siti (ICO EDUSHA, 2024)
The Islamic money market is an integral part of the Islamic financial system which aims to provide short-term investment instruments with principles in accordance with Islamic law. The basic concept of the Islamic money market focuses on transactions that are free from the elements of riba (interest), gharar (uncertainty), and maysir (gambling), and prioritizes the principles of justice and balance. Instruments used in the Islamic money market include sukuk (sharia bonds), sharia investment certificates (SBSN), and other sharia contracts, such as mudharabah and musyarakah, which provide opportunities for investors to earn profits in a halal manner. The Islamic money market also plays an important role in liquidity management for Islamic financial institutions, as well as providing investment alternatives for people who want to maintain their financial principles in accordance with Islamic teachings. With the rapid development of the Islamic money market, it is hoped that it can encourage inclusive and sustainable economic growth and strengthen the role of Islamic finance in the global economic system. Keywords: Islamic money market, sharia instruments, sukuk, liquidity, Islamic financial system.